Degradation of Junction Parameters of an Electrically Stressed NPN Bipolar Transistor - N. Toufik; F. Pélanchon; P. Mialhe (Active and Passive Electronic Components)
The effect of an electrical ageing on npn bipolar transistor has been studied. The current gain decreases substantially and the electrical properties are discussed. The emitter-base junction parameters are degraded during the electrical stress experiments. Both the amplitude and the rate of this degradation depend on the stress duration. The evaluation of these parameters allows to discuss hot carrier degradation process, to estimate the stress magnitude and to control the device.